2012
DOI: 10.2147/ijn.s27526
|View full text |Cite
|
Sign up to set email alerts
|

Protection of adenovirus from neutralizing antibody by cationic PEG derivative ionically linked to adenovirus

Abstract: Background:The generation of anti-adenovirus neutralizing antibody (NAb) in humans severely restricts the utilization of recombinant adenovirus serotype 5 (Ad5) vectors in gene therapy for a wide range of clinical trials. To overcome this limitation, we ionically complexed Ad5 with a newly synthesized copolymer, which we called APC, making an adenovirus shielded from NAb. Methods: APC, a cationic polyethylene glycol derivative, was synthesized via two steps of ring-opening copolymerization of ethylene oxide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Thus, for solid tumors and disseminated malignancies, an innovative procedure for a systemic and targeted delivery of OV is highly warranted. To enhance OV delivery to neoplastic tissue, several approaches have been developed, including: (i) viral capsid modification with the addition of polyethylene glycol (PEG) polymers to reduce immunogenicity and increase the circulation time in the blood; an approach that, however, resulted also in a significant reduction of the viral infectivity [ 5 , 7 ]; (ii) the use of drug carrier systems, such as liposomes [ 8 , 9 ], to increase the tumor-specific transduction of OV; a strategy that demonstrated poor serum stability of the particles and induced immune rejections in the host, thus preventing its further development [ 10 ]; (iii) recent studies reported that OV can be selectively delivered into neoplastic cells by tumor microparticles for virotherapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for solid tumors and disseminated malignancies, an innovative procedure for a systemic and targeted delivery of OV is highly warranted. To enhance OV delivery to neoplastic tissue, several approaches have been developed, including: (i) viral capsid modification with the addition of polyethylene glycol (PEG) polymers to reduce immunogenicity and increase the circulation time in the blood; an approach that, however, resulted also in a significant reduction of the viral infectivity [ 5 , 7 ]; (ii) the use of drug carrier systems, such as liposomes [ 8 , 9 ], to increase the tumor-specific transduction of OV; a strategy that demonstrated poor serum stability of the particles and induced immune rejections in the host, thus preventing its further development [ 10 ]; (iii) recent studies reported that OV can be selectively delivered into neoplastic cells by tumor microparticles for virotherapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, viral agents have not previously been isolated from tendons in horses. Zeng et al 30 used TEM to visualise adenovirus particles. Their TEM images suggest that adenoviruses are much smaller than the particles isolated in this experiment, with the approximate diameter being 70–90nm.…”
Section: Discussionmentioning
confidence: 99%
“…PEG is a long chain polymer, which when attached to Ads will protrude from the capsid in a hairlike manner [273]. Successful examples include O'Riordan [274], Wortmann et al [275] and Zeng et al [276], all of which found that they were able create shielded vectors able to evade neutralising anti-vector responses in vitro and in vivo. In vivo, PEG shielding also successfully prevented complement activation [190].…”
Section: Chemical Shieldingmentioning
confidence: 99%